2016
DOI: 10.1038/srep32993
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomes derived from human adipose mensenchymal stem cells accelerates cutaneous wound healing via optimizing the characteristics of fibroblasts

Abstract: Prolonged healing and scar formation are two major challenges in the treatment of soft tissue trauma. Adipose mesenchymal stem cells (ASCs) play an important role in tissue regeneration, and recent studies have suggested that exosomes secreted by stem cells may contribute to paracrine signaling. In this study, we investigated the roles of ASCs-derived exosomes (ASCs-Exos) in cutaneous wound healing. We found that ASCs-Exos could be taken up and internalized by fibroblasts to stimulate cell migration, prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
517
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 503 publications
(538 citation statements)
references
References 48 publications
20
517
0
1
Order By: Relevance
“…[7] Although the mechanism of the exosomes' role on proliferation and migration of fibroblasts was demonstrated, [8] no study has been conducted to identify the expressional changes of microRNAs, which play major role in various cellular responses, including proliferation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Although the mechanism of the exosomes' role on proliferation and migration of fibroblasts was demonstrated, [8] no study has been conducted to identify the expressional changes of microRNAs, which play major role in various cellular responses, including proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…[5] A study of stem cell transplantation therapy demonstrated that the role of MSCs in cell-tocell communication was exerted through a paracrine mechanism and that exosomes play a major role in this process. [6] Other findings also described that the conditioned media of ASC (ASC-CM) [7] or exosomes [8] were able to promote the migration of dermal fibroblasts during the process of wound healing. [7] Although the mechanism of the exosomes' role on proliferation and migration of fibroblasts was demonstrated, [8] no study has been conducted to identify the expressional changes of microRNAs, which play major role in various cellular responses, including proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more research should focus on ways to prevent and treat skin diseases. Various studies have identified an association between exosomes and skin diseases (23)(24)(25). For instance, melanoma cells secrete exosomes, which are abundant in the tumor microenvironment, to impact on the pathological process (26).…”
Section: Skinmentioning
confidence: 99%
“…In addition, adipose MSC-derived exosomes (ASCs-Exos) are internalized by fibroblasts to influence cell migration, proliferation and collagen synthesis (24). Histological analyses have indicated that the effect of ASCs-Exos on collagen is different between the early and later stages of wound healing, with increased collagen I and III synthesis at early stages and decreased collagen synthesis at later stages (24).…”
Section: Exosomes and Skin Wound Healingmentioning
confidence: 99%
“…Human ASCs were obtained and treated with an exosome precipitation solution [23]. Full-thickness wounds were created on the backs of Balb/c mice and four groups treatment groups administered: 1) no treatment control, 2) saline injected control, 3) exosome in saline subcutaneous injection, and 4) exosome in saline intravenously injected.…”
Section: Adipose-derived Mscsmentioning
confidence: 99%